Muçulmanos na cidade de Mogi das Cruzes, SP: inserção, estruturação e identidade. - Ferraz, Eduardo Henrique (2018)
In this research the Muslim religion in the city of Mogi das Cruzes is analyzed, starting from the cuts: insertion, structuring and identity. Through the field investigations and the theoretical bases used it was possible to verify that the process of insertion, structuring and identity of the Muslim immigrants in Mogi das Cruzes was due to the affirmation and persistence of certain aspects referring to values and principles directly related to family relations, cultural and religious of these immigrants. It can also be verified that the insertion of Islam in the city of Mogi das Cruzes, SP has in its structure and identity immigrants from Lebanon, having the Sunni Islamic religious follow. Thus, this work is a research developed from the analysis of the collection of testimonies and interviews of the pioneer immigrant Muslims, their descendants of first and second generation, lay religious leaders or not, also those who immigrated subsequently and natives who converted to Islam. It was sought through these testimonies to identify when the insertion of the religion occurred in the city, what were the paths covered for its structuring and how its current identity was configured. Through bibliographical research, aspects about the insertion, structuring and identity of the Islamic religion in Brazil, in Greater São Paulo and specifically in the city of Mogi das Cruzes, were presented.